DISCRIMINATION TOWARDS JESSE OWENS AS PORTRAYED IN THE RACE (2016) FILM - Purnawati, Novita Diah; Kuncara, Singgih Daru; Sudirman, Eka Pratiwi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
ABSTRACT Discrimination is a social problem that often occurs in society. This study focused on discrimination issues towards Jesse Owens as the main character in the Race film. The purposes of this research are to identify the types of discrimination and the types of responses against discrimination that happens to Jesse Owens in the Race film. The researcher used a qualitative method and mimetic approach in this research. To identify the types of discrimination and the types of responses against discrimination, the researcher used Feagin and Sikes' theory. There were four types of discrimination that occurred towards Jesse Owens, namely avoidance, rejection, verbal attacks, and the last are other threats and harassment. From all the types of discrimination found, verbal attacks were the most common type found in this research. In addition, there was no type of police threats and harassment in this film, because Jesse Owens rarely interacts with the police. Besides, there were two types of responses against discrimination shown by Jesse Owens in the Race film, namely withdrawal and resigned acceptance. From all the types of responses against discrimination, resigned acceptance is the most common type in this research. In addition, there was no verbal confrontation and physical confrontation in this film because the discrimination stopped after he did the resigned acceptance to against it. All of the discrimination in this study is depicted through Jesse Owens as the victim in this film.